Regulation of TNF-α-Induced Microvascular Endothelial Cell Hyperpermeability by Recombinant Bcl-xL - Sawant, Devendra A. (2013)
BACKGROUND: Tumor necrosis factor-α (TNF-α), a cytotoxic cytokine, induces endothelial cell barrier dysfunction and microvascular hyperpermeability leading to tissue edema, a hall mark of traumatic injuries. The objective of this study was to determine if Bcl-xL, an anti-apoptotic protein, would regulate and protect against TNF-α-mediated endothelial cell barrier dysfunction and microvascular hyperpermeability. METHODS: Rat lung microvascular endothelial cells (RLMECs) were grown as monolayers on Transwell membranes, and FITC-albumin-flux (5mg/ml) across the monolayer was measured fluorometrically to indicate change in monolayer permeability. The RLMEC adherens junctional integrity and actin cytoskeleton were studied by β-catenin immunofluorescence, and using rhodamine phalloidin dye, respectively. Pretreatment of caspase-8 inhibitor (Z-IETD-FMK, 100μM) for 1 hour and transfection of BID siRNA (10μM) for 48 hours, were performed to study their respective effects on TNF-α-induced (10ng/ml; 1 hour treatment) monolayer permeability. Recombinant Bcl-xL protein (2.5μg/ml) was transfected in RLMECs for 1 hour, and its effect on permeability was demonstrated using permeability assay. Caspase-3 activity was assayed fluorometrically. RESULTS: Z-IETD-FMK pretreatment protected the adherens junctions and decreased TNF-α-induced monolayer hyperpermeability. BID siRNA transfection attenuated TNF-α-induced increase in monolayer permeability. Recombinant Bcl-xL protein showed protection against TNF-α-induced actin stress fiber formation, an increase in caspase-3 activity, and monolayer hyperpermeability. CONCLUSIONS: Our results demonstrate protective effects of recombinant Bcl-xL protein against TNF-α-induced endothelial cell adherens junction damage and microvascular endothelial cell hyperpermeability. These findings support the potential for Bcl-xL-based drug development against microvascular hyperpermeability and tissue edema.